Screening for cognitive impairment and dementia among elderly persons attending a tertiary hospital - Pandey, Srijana; Pandey, Srijana; Lama, Ishwori (Nepal Medical College Journal, 2023)
Cognitive impairment is debilitating condition for elderly in their activities of daily living which can cause problem to self, others and society. Therefore, the researcher aims to screen the cognitive impairment among elderly population at Tertiary Hospital. Cross sectional, descriptive and exploratory design with Purposive sampling technique was used among elderly population at OPD of Tertiary hospital. Mini-mental status examination, activities of daily living, instrumental activities of daily living were used for screening cognitive impairment and dementia. The interview dates were set up for 15 days. Sampling procedure included quota of 20 cases per day and thus, the sample was 300 elderly. Total sample after four persons denied to participate was 296. The mean age of elderly respondents were 71.58 (±5.09). The study revealed that there was no cognitive impairment among 67.6%, mild cognitive impairment among 25.7% and moderate cognitive impairment among 6.8%. The activities of daily living in majority of respondents were 95.3% in full function and least 1% were in severe functional impairment. Instrumental activities of daily living indicated that three-fourths of the respondents 76.7% had high function, 16.2% needed assistance and 7.1% had low function. Age, living with status is significantly associated with cognitive impairment. Screening of cognitive impairment is necessary to identify the impairment among elderly which enhances the awareness of cognitive impairment.